PENULISAN PARAGRAF DEDUKTIF DALAM BENTUK AKSARA LAMPUNG - Sabila, Amy (JURNAL PESONA, 2018)
AbstractThe objective of the study is to describe writing of deductive paragraphs into Lampung script. This research used qualitative descriptive method including collecting and analysis data. The first step, researcher used written tests and notes as the main data. The data analysis in this research is Padan method. The researcher got the result data. First, inaccuracy the use of the script "a, nga, nya, and ya", letter rejunjung "ar", keleniah "ah" and tekelubang "ang", and use of fullstop. Second data cannot distinguish datas bicek "e" andÂ  datas hulan "e", the use of "a, ya, and ha" script, the use of rejunjung "ar" and redatas "an", and disappearance of word âwill, of and stay ". In data 3 inaccurate use of "a, nga, ha, and ya", rejunjung "ar", tekelubang âangâ, bitan "u" and datas hulan "e" and fullstop. For data 4 did not found error.Â Â Â Â Â Â Â Â Â  Keywords: Writing, Deductive Paragraph, Lampung Script